The Role of Entrepreneur Cognition on Core Rigidity - Guo, Yan; Huang, Pei-Wen; Chou, Meihui; Fang, Shih-Chieh; Tsai, Fu-Sheng (Frontiers in Psychology, 2022)
Against the backdrop of economic internationalization and market globalization, the world has witnessed faster competitive contents with a more dynamic market environment, more rapid technological innovation, and more diverse customer needs. It is thus a focus for every enterprise, especially those led by entrepreneurs, to maintain the sustainability of competitive advantage and dynamically transform core capacity to avoid rigidity. This paper introduces the process of the deepened rigidity in Wuxi Suntech Company, which was due to the wrong cognition of Shi Zhongrong and his teams, who managed or failed to respond to the rigidity encountered by the company during different periods. The rigidity of its capacity is believed to be caused by the cognitive errors of the entrepreneur and his team facing every period of potential rigidity, which makes them fail to deal with it (or choose the wrong methods), thus leading to complete rigidity. This paper intends to explain how rigidity takes shape from the cognitive aspect of senior managers, which may serve as illuminations for similar enterprises led by entrepreneurs.